RETENTION AND ATTRITION AMONG AFRICAN AMERICANS IN THE STAR*D STUDY: WHAT CAUSES RESEARCH VOLUNTEERS TO STAY OR STRAY?. Issue 11 (30th May 2013) - Murphy, Eleanor J.; Kassem, Layla; Chemerinski, Anat; Rush, A. John; Laje, Gonzalo; McMahon, Francis J.
<x xml:space="preserve">Abstract</x> Background High attrition rates among African‐Americans (AA) volunteers are a persistent problem that makes clinical trials less representative and complicates estimation of treatment outcomes. Many studies contrast AA with other ethnic/racial groups, but few compare the AA volunteers who remain in treatment with those who leave. Here, in addition to comparing patterns of attrition between African Americans and Whites, we identify predictors of overall and early attrition among African Americans. Method Sample comprised non‐Hispanic African‐American (n = 673) and White (n = 2, 549) participants in the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study. Chi‐square tests were used to examine racial group differences in reasons for exit. Multivariate logistic regression was used to examine predictors of overall attrition, early attrition (by level 2) and top reasons cited for attrition among African Americans. Results Both African‐American and White dropouts most commonly cited noncompliance reasons for attrition during the earlier phases of the study, while citing reasons related to efficacy and medication side effects later in the study. Satisfaction with treatment strongly predicted overall attrition among African Americans independent of socioeconomic, clinical, medical or psychosocial factors. Early attrition among African American dropouts was associated with less psychiatric comorbidity, and higher perceived physical functioning but greater severity of clinician‐rated depression. Conclusions Compliance, efficacy, and side effects are important factors that vary in relative importance during the course of a clinical trial. For African Americans in such trials, retention strategies should be broadened to emphasize patient engagement and satisfaction during the critical periods immediately following enrollment and treatment initiation.